Outcome of Transurethral Incision Around the Ureteric Orifice to Remove the Bladder Cuff Versus Open Excision of Bladder Cuff in Patients Undergoing Nephroureterectomy for Upper Urinary Tract Transitional Cell Carcinoma (Bangladesh Journal of Urology, 2023)
Introduction: Radical nephroureterectomy with excision of ipsilateral bladder cuff is the gold standard treatment for high risk upper urinary tract transitional cell carcinoma. This procedure requires two incisions. However endoscopic detachment of distal ureter and bladder cuff by transurethral incision and removal of kidney requires single abdominal incision. Though the intention is to decrease morbidity by avoiding a second lower abdominal incision, argument exists regarding oncological outcomeMethods: This Quasi-Experimental study was conducted from September, 2020 to August, 2022 in the department of urology, Bangabandhu Sheikh Mujib Medical University. Here 15 patients were in Group A who underwent transurethral incision around the ureteric orifice to remove the bladder cuff (Pluck technique) with single abdominal incision for open radical nephroureterectomy and 17 patients were in Group B who underwent open extravesical approach for excision of cuff of bladder during radical nephroureterectomy making two abdominal incisions. Both techniques were compared to assess the operative and oncological outcome.Results: Operative time was longer in group B (p